2023
DOI: 10.1186/s12954-023-00785-y
|View full text |Cite
|
Sign up to set email alerts
|

‘This is hardcore’: a qualitative study exploring service users’ experiences of Heroin-Assisted Treatment (HAT) in Middlesbrough, England

Abstract: Background Heroin-Assisted Treatment (HAT) is well evidenced internationally to improve health and social outcomes for people dependent on opioids who have not been helped by traditional treatment options. Despite this evidence base, England has been slow to implement HAT. The first service outside of a trial setting opened in 2019, providing twice-daily supervised injections of medical-grade heroin (diamorphine) to a select sample of high-risk heroin users in Middlesbrough. This paper explores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Regarding treatment-deterring perceptions, our results concur with findings from the UK [27], Australia [24], and Belgium [28] in which people living with OUD were reluctant to start iOAT due to the daily supervised application. Procedural factors such as daily visits are known to jeopardize the initiation and maintenance of both oOAT [37] and iOAT [12,38].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Regarding treatment-deterring perceptions, our results concur with findings from the UK [27], Australia [24], and Belgium [28] in which people living with OUD were reluctant to start iOAT due to the daily supervised application. Procedural factors such as daily visits are known to jeopardize the initiation and maintenance of both oOAT [37] and iOAT [12,38].…”
Section: Discussionsupporting
confidence: 87%
“…Individuals unresponsive to oOAT were motivated to start iOAT as a result of perceived benefits such as the reduction of street heroin use and criminal activities, achieving stability and normality, improving their health status, and having a dependable source of safe opioids [21][22][23][24][25]. While this is comparable to studies on oOAT, recent qualitative enquiries additionally found perceptions of the ineffectiveness of oOAT and the option to inject as encouraging for iOAT initiation [26,27]. Although less extensively studied, there are some data that represent perceptions that deter enrolment in iOAT.…”
Section: The Importance Of Perceptionsmentioning
confidence: 87%
See 3 more Smart Citations